Archaic Spindle Whorls of Cowboy Cave and Walters Cave in Utah. Issue 3 (3rd July 2019) - Hilbish, Judy F.
Abstract : The theory that spindle whorls were used in the Archaic Southwest is proposed to explain the presence of spindle whorls at the Archaic hunter-gatherer of sites Cowboy and Walters Caves. The objects in question were evaluated at the Natural History Museum of Utah to determine if they have the characteristics of whorls. Also, cordage from these caves is compared with cordage from other sites to determine if it could be spindle spun as opposed to thigh-spun. If so, this would support the theory that the objects in question were used as whorls. The use of spindle whorls by hunter-gatherers is not new but finding their use in the hunter-gatherers of the Archaic Southwest is.